Phraseologisms related to the names of hats in the Kazakh and Turkish languages: Ethnolinguistic nature - Turganbayeva, К.М.; Sarekenova, Қ.Қ.; Togyzbai, Н.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2026)
The article analyzes the content features, semantic structure and cultural background of phraseology related to the names of hats in the Kazakh and Turkish languages, their similarities and differences are considered from an ethnolinguistic point of view. The research work aims to contribute to the disclosure of common linguistic archetypes and cultural continuity of the Turkic peoples, as well as to clarify the reflection of phraseology in relation to national identity. As an object of study, stable expressions derived from traditional headdress names such as Berik, turban, fes, takke, külah, which are widely used in the languages of both peoples, were taken. Especially in the composition of phraseology, the direction of action (for example, a Burk was thrown into the air, a Burk was hit on the ground) and its connection with emotions are characterized by close interweaving with cultural content. At the same time, it is proved that stable expressions in Turkish, such as Fesini air Atatürk, Takke çalı, kel göldü, Küllah takmak, also have a symbolic meaning, expressing the national attitude and norms of social attitudes. As a result of the study, in addition to similarities in the structure and content of Kazakh and Turkish phraseology, differences are also revealed that reflect the historical and cultural identity of each nation. This, in turn, will allow us to identify the ethnolinguistic commonality of Turkic languages and reveal the cognitive potential of phraseology. The methods of comparative, semantic and ethnolinguistic analysis used in the article allow us to systematically differentiate the phraseological fund of the two peoples. Through this, important scientific conclusions are made aimed at recognizing the national identity, cultural code, historical memory and system of cognition through language.